2021
DOI: 10.3390/cancers13112521
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Prediction Performance by Add-On Combining Circulating Tumor Cell Count, CD45neg EpCAMneg Cell Count on Colorectal Cancer, Advance, and Metastasis

Abstract: Conventional circulating tumor cell (CTC) enumeration could ignore the CTCs more relevant to cancer metastasis. Thus, negative selection CTC enumeration was proposed, by which information on two cellular biomarkers (numbers of CTCs and CD45neg EpCAMneg cells) can be obtained. By combining this approach with the conventional biomarker carcinoembryonic antigen (CEA), this study aimed to explore whether any combination of these biomarkers could improve the predictive performance for colorectal cancer (CRC) or its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A recent study revealed the diagnostic value of CTC enumerations and found that improved accuracies of AUC in predicting metastatic CRC samples were obtained by analyzing the combination of CEA and CTCs, rather than by CEA alone. 56 A strong association existed between patients with CTCs and cancer stage as well as the individual T, N, and M staging. High CEA levels are also correlated in patients with five or more CTCs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study revealed the diagnostic value of CTC enumerations and found that improved accuracies of AUC in predicting metastatic CRC samples were obtained by analyzing the combination of CEA and CTCs, rather than by CEA alone. 56 A strong association existed between patients with CTCs and cancer stage as well as the individual T, N, and M staging. High CEA levels are also correlated in patients with five or more CTCs.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study revealed the diagnostic value of CTC enumerations and found that improved accuracies of AUC in predicting metastatic CRC samples were obtained by analyzing the combination of CEA and CTCs, rather than by CEA alone. 56…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, CTCs might undergo an epithelial-tomesenchymal transition in metastatic disease after which their EpCAM expression is downregulated. These EpCAM − CTCs are considered as "atypical CTCs" and can also be analyzed using our protocol [25,26]. However, given the uncertain clinical significance of EpCAM − CTCs in patients with esophageal cancer, we only defined CTCs as Hoechst + CD45 − EpCAM + cells in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, only a small portion of CTCs can undergo metastasis, while multiple mechanisms in heterogeneous CTCs facilitate their metastatic potential by driving CTC interactions with immune and stromal cells[ 62 ]. First, Chiu et al [ 63 ] showed that, compared with carcinoembryonic antigen (CEA) alone, CTC detection increases the power of the area under the receiver operating characteristic curve for predicting mCRC (0.7800 vs 0.8378). Surprisingly, Le et al [ 64 ] showed that CTCs were not associated with the size or number of metastases, as determined after previously administered drug therapy, or disease-free survival (DFS).…”
Section: Mcrc and Metastatic Cascadesmentioning
confidence: 99%